The protective effects of chrysin and flunixin meglumine against excess copper in male rats - Seven, Pinar Tatli; Baykalir, Burcu Gul; Seven, Ismail; Ak, Tuba Parlak; Basak, Nese; Gulluoglu, Hakan (Tubitak Scientific & Technological Research Council Turkey, 2018)
Thirty-six Sprague Dawley male rats were housed in individual cages and randomly divided into six groups: control, copper sulfate (Cu; 500 ppm body weight (BW)/day), flunixin meglumine (FM; 2.2 ppm BW/day), chrysin (chrysin; 50 ppm BW/day), copper sulfate + FM (Cu + FM; 500 ppm BW/day of copper sulfate and 2.2 ppm BW/day of FM), and copper sulfate + chrysin (Cu + Chrysin; 500 ppm BW/day of copper sulfate and 50 ppm BW/day of chrysin). Feed intake (FI) in the Cu + Chrysin group significantly increased in comparison with that of the Cu group (P < 0.01). Cu excess significantly increased malondialdehyde, indicating oxidative stress. Chrysin and FM administration significantly decreased malondialdehyde levels and increased the superoxide dismutase and catalase activities in the liver and kidney tissues (P < 0.001). Serum TNF-a levels were significantly lower in the Cu + FM and Cu + Chrysin groups in comparison to the Cu group (P < 0.001). It was seen that FM and chrysin treatments alleviated degeneration, necrosis, and apoptosis in the liver and kidney tissues of the Cu-treated rats. Chrysin appeared to ameliorate the adverse effects on FI and liver and kidney tissues by scavenging where the free radicals are located and increasing the activity of antioxidants.
Keywords: Antioxidant status; body weight change; chrysin; copper; flunixin meglumine; histological changes